2022
DOI: 10.3390/ijfs10030060
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internal Audit to Reduce the Effects of Creative Accounting on the Reliability of Financial Statements in the Jordanian Islamic Banks

Abstract: The purpose of this study is to look into the role of internal audit (IA) in reducing the effects of creative accounting (CA) on financial statement reliability in Jordanian Islamic Banks. The research study used the survey methodology to examine the role of internal audit (including independence and objectivity, verifiability, professional care, and neutrality) to reduce the effects of CA on the reliability of financial statements in Jordanian Islamic Banks. The population consists of all practicing auditors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…This study builds on the recommendations of the literature review on earnings management by Walker (2013) who recommended expanding research methods to include qualitative and quantitative methods rather than focusing on archival data. This study complements the results of previous relevant studies that demonstrated the use of EMP in Jordan (Shana'a et al 2023;Alhadab et al 2021;Alzoubi, 2016;Aburisheh et al 2022;Abbadi et al 2016;Matar et al 2017;Jarah et al 2022;Saleem, 2019) by exploring the complementary roles of standard setters, regulators and professional associations in curbing EMP. Therefore, this study aims to provide evidence from developing countries about the phenomenon of earnings management and how it is dealt with by regulators and professional institutes, in contrast to developed countries that have strict regulatory arms in supervising the work of auditors, especially in listed companies.…”
Section: Research Statement and Contributionsupporting
confidence: 82%
“…This study builds on the recommendations of the literature review on earnings management by Walker (2013) who recommended expanding research methods to include qualitative and quantitative methods rather than focusing on archival data. This study complements the results of previous relevant studies that demonstrated the use of EMP in Jordan (Shana'a et al 2023;Alhadab et al 2021;Alzoubi, 2016;Aburisheh et al 2022;Abbadi et al 2016;Matar et al 2017;Jarah et al 2022;Saleem, 2019) by exploring the complementary roles of standard setters, regulators and professional associations in curbing EMP. Therefore, this study aims to provide evidence from developing countries about the phenomenon of earnings management and how it is dealt with by regulators and professional institutes, in contrast to developed countries that have strict regulatory arms in supervising the work of auditors, especially in listed companies.…”
Section: Research Statement and Contributionsupporting
confidence: 82%
“…The findings (Jarah & Iskandar, 2019) demonstrated a substantial link between AIS features and financial performance. A significant between internal audit and supply chain management was found in a study by (Jarah et al, 2022). According to the findings of Al , project risk management arts moderate the influence of project initiation, planning, execution, monitoring and control, closing, and management processes on successful project implementation.…”
Section: Hypothesis Developmentmentioning
confidence: 95%
“…Annual reports are comprehensive sources of information that disclose financial and non-financial aspects of the banks' operations, including CSR-related disclosures. The data for the selected Jordanian Islamic banks from 2010 to 2022 were obtained from their publicly available annual reports on the Amman Stock Exchange (Jarah et al, 2022).…”
Section: Data Collectionmentioning
confidence: 99%